An analysis of correlation between oceanographic parameters and productivity of trammel net in Prigi, Trenggalek - Syifa', Sea Fadlina Hidayatus; Perdanawati, Rizqi Abdi; Setiawan, Fajar (UIN Sunan Ampel Surabaya, 2021)
Prigi, Trenggalek is a potential fishery area located in the southern part of the East Java. Most fishers in Prigi uses trammel net as a capture device. The purpose of this research is to analyze the correlation of oceanographic parameters on the production of trammel net in Prigi’s fishing ground. The data used in this research are temperature, pH, salinity, velocity of currents, depth, and trammel net production during 35 trips. Oceanographic parameters in the fishing ground are temperature ranges from 26°C - 31°C, pH ranges from 7 – 9, salinity ranges from 25‰ - 35‰, current velocity range 0.13 m/s - 0.39 m/s, and the water depth ranges from 10 - 18 m. Variability from trammel net production are long tongue sole (Cynoglossus sp), crab (Portunus sp), endeavour shrimp (Metapenaeus sp), sea snail (Bufonaria sp), common ponyfish (Leiognathus sp), japanese threadfin bream (Nemipterus sp), squid (Loligo sp), and giant tiger prawn (Penaeus sp) with total production 302.2 kg. Correlation between oceanographic parameters and trammel net production are high for the current velocity with correlation value 0.78, and medium for depth and temperature with correlation value are 0.56 and 0.45, respectively. Correlation between salinity and pH with trammel net production are low and very low with correlation value -0.23 and 0.002, respectively.